PENGARUH DIGITAL MARKETING DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN UD SURYA PERKASA MOTOR - Lidya Syayyidatun Nisa' (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine the influence of TikTok live streaming, discounts, and celebrity endorsements on skincare product purchasing decisions, with a case study on Skintific products in Lamongan. In today's digital era, marketing strategies through social media such as TikTok are increasingly developing, especially through interactive live streaming features, discounts as a consumer attraction, and celebrity endorsements that increase trust in products. This study uses a descriptive quantitative method with a data collection technique through a questionnaire distributed to 155 respondents, namely students of the Faculty of Economics and Business, Lamongan Islamic University who know or have purchased Skintific products. The data were analyzed using multiple linear regression with the help of SPSS version 21. The results showed that the three independent variables, namely TikTok live streaming, discounts, and celebrity endorsements, had a positive and significant effect on purchasing decisions. This finding strengthens that social media-based digital marketing strategies can increase consumer interest and decisions in purchasing skincare products.